2022
DOI: 10.1109/tpami.2020.3045007
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Deep Learning Techniques for Video Prediction

Abstract: The ability to predict, anticipate and reason about future outcomes is a key component of intelligent decision-making systems. In light of the success of deep learning in computer vision, deep-learning-based video prediction emerged as a promising research direction. Defined as a self-supervised learning task, video prediction represents a suitable framework for representation learning, as it demonstrated potential capabilities for extracting meaningful representations of the underlying patterns in natural vid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(103 citation statements)
references
References 148 publications
0
103
0
Order By: Relevance
“…Image prediction was performed in [30] using a visible light image and a stochastic variational video prediction (SV2P) method. In a review study [31], the datasets from 2004 to 2019 used in image prediction were compared with the image prediction models that were released between 2014 and 2020. In the survey in [32], studies on and datasets for image prediction were explained.…”
Section: Prediction Of Next Sequential Framesmentioning
confidence: 99%
“…Image prediction was performed in [30] using a visible light image and a stochastic variational video prediction (SV2P) method. In a review study [31], the datasets from 2004 to 2019 used in image prediction were compared with the image prediction models that were released between 2014 and 2020. In the survey in [32], studies on and datasets for image prediction were explained.…”
Section: Prediction Of Next Sequential Framesmentioning
confidence: 99%
“…Comprehensive reviews on video frame prediction methods can be found in [7,8]. Methods covered in these reviews can be classified according to their network architecture, prediction methodology, and loss function used in training.…”
Section: Frame Predictionmentioning
confidence: 99%
“…This approach uses the generated optical flow [20] to guide the connection structure in the network, and the point in the convolution structure is connected to points with a higher correlation instead of a fixed number of surrounding points. Many spatiotemporal prediction methods [21][22][23] have regarded radar echo extrapolation as one of the tasks to evaluate the spatiotemporal prediction ability of their methods. Wang et al [24] proposed a spatiotemporal prediction method called PredRNN, which makes the spatial features of each layer of ConvLSTM interact in time series.…”
Section: Introductionmentioning
confidence: 99%